Developing a National Strategy for Advancing Feed and Forage Resources in Tunisia - Frija, Aymen; Alary, Veronique (CGIAR, 2023)
CGIAR Initiatives on Agroecology and Livestock and Climate held a national workshop on “Developing a National Strategy for promoting Feed and Forage Resources in Tunisia” in March 2023. ICARDA, and its key partners in Tunisia [namely the Bureau of livestock and pastures (Office de l’Elevage et des Pâturages), and the Institution of Agricultural Research and Higher Education (IRESA)] organized the event that aimed at developing a national road map to promote and upgrade the sector of animal feed resources at the horizon of 2035. The main purpose is to reduce the feed sector dependence on importations and enhance the use of local feed resources through increased production, storage, and processing investments.